Double trouble for prostate cancer: synergistic action of AR blockade and PARPi in non-HRR mutated patients - Giesen, Alexander; Baekelandt, Loïc; Devlies, Wout; Devos, Gaëtan; Dumez, Herlinde; Everaerts, Wouter; Claessens, Frank; Joniau, Steven (Frontiers in Oncology, 2023)
Prostate cancer (PCa) is the most common cancer in men worldwide. Despite better and more intensive treatment options in earlier disease stages, a large subset of patients still progress to metastatic castration-resistant PCa (mCRPC). Recently, poly-(ADP-ribose)-polymerase (PARP)-inhibitors have been introduced in this setting. The TALAPRO-2 and PROpel trials both showed a marked benefit of PARPi in combination with an androgen receptor signaling inhibitor (ARSI), compared with an ARSI alone in both the homologous recombination repair (HRR)-mutated, as well as in the HRR-non-mutated subgroup. In this review, we present a comprehensive overview of how maximal AR-blockade via an ARSI in combination with a PARPi has a synergistic effect at the molecular level, leading to synthetic lethality in both HRR-mutated and HRR-non-mutated PCa patients. PARP2 is known to be a cofactor of the AR complex, needed for decompacting the chromatin and start of transcription of AR target genes (including HRR genes). The inhibition of PARP thus reinforces the effect of an ARSI. The deep androgen deprivation caused by combining androgen deprivation therapy (ADT) with an ARSI, induces an HRR-like deficient state, often referred to as “BRCA-ness”. Further, PARPi will prevent the repair of single-strand DNA breaks, leading to the accumulation of DNA double-strand breaks (DSBs). Due to the induced HRR-deficient state, DSBs cannot be repaired, leading to apoptosis.